Combining GPS tracking and survey data to better understand travel behavior of out-of-bounds skiers. (September 2020) - Sykes, John; Hendrikx, Jordy; Johnson, Jerry; Birkeland, Karl W.
Abstract: Our research seeks to expand existing knowledge of travel behavior and decision-making in avalanche terrain. We have done this by using GPS tracking to observe the travel behavior of out-of-bounds (OB) skiers and collecting survey data to investigate their terrain choices. We sampled participants in the field by distributing hand-held GPS units and surveys along the southern boundary of Bridger Bowl Ski Area, Southwest Montana, USA. In total, we used data from 136 participants that volunteered over the course of 19 field days, from February 2017 to February 2018. We analyzed the resulting GPS data using a GIS, and we derived terrain metrics from elevation and land cover data. We fit a multiple linear regression model using GPS track downhill starting distance from the ski area boundary as the response variable and survey responses, interaction with complex avalanche terrain (as defined using the Avalanche Terrain Exposure Scale), weather conditions, and avalanche hazard level as explanatory variables. This approach evaluates travel behavior as a function of human factors, terrain, weather, and snowpack, providing a holistic perspective on decision-making drivers. Our results show that gender ( female ), formal avalanche education, and perception of avalanche mitigation are statistically significant (p < 0.05) survey responses which indicate that participants travel further from the ski area boundary before descending Saddle Peak, which effects individuals avalanche terrain exposure. Downhill starting distance is also significantly correlated with time and distance in complex avalanche terrain (p < 0.05) . Our results provide a case study of the terrain preferences and avalanche awareness of OB skiers and highlight specific "human factors" that are correlated with terrain selection. Two practical applications of this research are: 1) tailoring of targeted avalanche education outreach based on our results specific to the OB setting, and 2) designing new signage to illustrate the avalanche terrain near the ski area boundary for skiers who are inexperienced in the backcountry or unfamiliar with the specific area. Highlights: Applied Avalanche Terrain Exposure Scale to quantify risk due to avalanches. Low cost method for GPS data collection on recreational travel behavior. Skiers less prepared and knowledgeable about avalanche danger than expected. High incidence of skiers travelling without a partner in backcountry terrain. Survey assessed human factors correlated with higher risk travel behavior.